Harmonisasi Pengetahuan: Menelusuri Interaksi Islam dan Filsafat dalam Pengembangan Ilmu Pengetahuan: MENELUSURI INTERAKSI ISLAM DAN FILSAFAT DALAM PENGEMBANGAN ILMU PENGETAHUAN - Rian Hidayat (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2024)
This research aims to comprehend the roles of Islam and philosophy in the development of scientific knowledge. Islam and philosophy play significant roles in shaping worldviews, values, and epistemological approaches that underpin the development of scientific knowledge. The study employs a descriptive-analytical approach to explore the relationships among religion, philosophy, and science. Data is collected through a literature review encompassing relevant primary and secondary sources related to the research topic. Data analysis involves the collection, classification, and interpretation of pertinent information. The findings indicate that Islam exerts a strong influence on the development of scientific knowledge through moral perspectives, ethics, and views on the universe. Islam often provides a value framework that shapes the motivation and goals of research, influencing ethical decisions in scientific practices. On the other hand, philosophy also plays a crucial role in the development of scientific knowledge through studies of epistemology, logic, and research methods. Philosophy provides a theoretical and conceptual foundation supporting understanding, reasoning, and critical reflection in scientific practice. The interconnectedness of Islam, philosophy, and science reflects a dialogue and interaction between religious beliefs, rational philosophy, and empirical understanding. The integration of these aspects allows for the holistic development of scientific knowledge, combining spiritual, intellectual, and empirical aspects in the understanding and explanation of natural phenomena.